Effective Programs in Elementary Mathematics: A Meta-Analysis. (January 2021) - Pellegrini, Marta; Lake, Cynthia; Neitzel, Amanda; Slavin, Robert E.
This article reviews research on the achievement outcomes of elementary mathematics programs; 87 rigorous experimental studies evaluated 66 programs in grades K–5. Programs were organized in six categories. Particularly positive outcomes were found for tutoring programs (effect size [ES] = +0.20, k = 22). Positive outcomes were also seen in studies focused on professional development for classroom organization and management (e.g., cooperative learning; ES = +0.19, k = 7). Professional development approaches focused on helping teachers gain in understanding of mathematics content and pedagogy had little impact on student achievement. Professional development intended to help in the adoption of new curricula had a small but significant impact for traditional (nondigital) curricula (ES = +0.12, k = 7), but not for digital curricula. Traditional and digital curricula with limited professional development, as well as benchmark assessment programs, found few positive effects.